Design of Inversion Modeling 1-D Gravity Data Using a Method of Singular Value Decomposition (SVD) Based on Matlab - Irwansyah .; Teuku Khairuman; Nazli Ismail (PSI-Aceh, 2013)
The study about design of Inversion Modeling 1-D Gravity Data using a method of Singular Value Decomposition (SVD) based on Matlab has been done. This study is aimed to design the modeling program of 1-D gravity data using SVD method based on Matlab and than apply the program for subsurface investigation based on contras density of the target body. The SVD method was used to solve the inversion code by applying truncation method of the data into some eigen values in order to resolve a better model. Gravity data used for inversion modeling is data generated from the forward modelling code. Inversion modeling program has been tested for several models such as with variation depth and its contrast density vertical fault. The result mostly show a small data error is equal to 0,9908 mGal.